In the Mood for Likes: A Longitudinal Study of Civil Society Organizations’ Emotional Communication on Social Media - Nils Gustafsson; Nils Holmberg; Noomi Weinryb; Anders Olof Larsson (Social Media + Society)
Emotional communication, especially through social media platforms, has become a contemporary populist threat. While this phenomenon has been studied in for example news media and social movements, we know less about its influence on civil society organizations, despite their pluralism being a centerpiece in a vibrant democracy. More specifically, we do not know if social media make civil society organizations more isomorphic and thus decreasing the diversity of their emotional communication over time. This question is relevant given the broad range of organizational fields that civil society engages in, as well as the documented push toward especially extreme positivity on social media platforms. Given this background, the article explores the use of positive and negative sentiment, as well as of sentiment intensity, over time in the social media communication of different organizational fields of civil society. We employ sentiment analysis to analyze approximately 100,000 organizational posts on Facebook from 125 Swedish nonprofit organizations during 2015–2020. We find that the pluralism of civil society organizations across different fields, as regards emotional communication, is retained over time, thus not threatening the pluralism of civil society in this way. In addition, emotional communication, and especially positivity, increases over time in all fields in absolute terms. However, considering post length, the relative amount of emotional communication exhibits less of an increase. Rather, across all fields there is an unexpected isomorphism relating to posts becoming longer, while enticing less user engagement. This development, rather than the lack of pluralism, raises democratic concerns.